A STUDY OF THE EFFECTS OF MASS MEDIA AS AN EFFECTIVE FACTOR OF EDUCATION - Bharati, Reena; Ahmad, Jarrar (International Journal of Research -GRANTHAALAYAH, 2025)
Mass media, or mass media, is playing a very important role in the field of education in today's modern society. These media are not only important in disseminating information but they also influence people's attitudes, behavior, and level of knowledge. Mass media such as television, radio, Internet, newspapers, and magazines play a major role in disseminating knowledge and information. Through these media, education can be delivered to a wide audience. For example, educational television programs or online courses can benefit millions of students around the world. Open Educational Resources (OERs) available through the Internet have made the flow of knowledge even more accessible, allowing students to access high-quality content on a variety of subjects. Mass media has also greatly expanded the reach of education. Education through television, such as Doordarshan's 'Vidya' channels in India, is spreading education even in rural and backward areas. In addition, the Internet has popularized online education, allowing students to continue their studies from any location. Especially during the COVID-19 pandemic, online learning became the only option and mass media played a significant role in this. Mass media has also improved the quality of education. High-quality educational programs, documentaries, and educational podcasts have provided diverse and interesting learning materials for students. These resources enhance the cognitive abilities of students and make them more enthusiastic about their studies. In addition, online seminars and webinars conducted by experts have given students the opportunity to gain in-depth and up-to-date knowledge.